Avaliação da exposição à radiação do médico cardiologista em procedimentos intervencionistas - Moreira, Antonio Carlos [UNIFESP] (2019)
Objective: Estimate the equivalent dose received in the eye region and in different regions of the cardiologist body in diagnostic (CATE) and therapeutic procedures (ATC), using DIS-Mirion Technologies (InstadoseTM) and thermoluminescent (TLD100) dosimeters. Methods: The study was performed in a cardiovascular exams room in which the Innova-GE angiography is installed with table-mounted lead drapes and without ceiling suspended screen. Dosimeters were fixed, together, in the following cardiologist body regions: next to the eyes region (left and right), chest level (without lead apron protection), extremity (left ankle). A set was also fixed in the center of equipment gantry to measure the scattered radiation in the environment. The procedures were performed with lead glasses but the doses were evaluated without this protection. The occupational doses at the cardiologist were registered during 81 procedures, 60% catheterisms and 40% angioplasties. The patient dose parameters presented on the monitors at the end of the procedures were registered, as well as their anthropometric data. The average exposure time was 10 minutes for CATE and 20 minutes for ATC. Results: The 3rd quartile and [median] values for accumulated kerma and KAP during ATC procedures were: 3349 [2083] mGy and 204.9 [127.3] Gy.cm2 and during CATE: 1687 [1039] mGy and 117.4 [77.5] Gy.cm2. The statistics analysis of doses comparison between the TL and InstadoseTM dosimeters, in the CATE and ATC procedures, showed that there were no significative differences disregarding the situations wherein the doses were around the InstadoseTM sensitivity threshold. It permits consider the InstadoseTM as effective as TLD in occupational monitoring. Considering TL on left eye region, 3rd quartile and [median] values for CATE procedures were 0.097; [0.069] mSv and 0.120; [0.096] mSv for InstadoseTM. In the ATC procedures 3rd quartile and [median] values for TL and InstadoseTM were, respectively: 0.147; [0.116] mSv and 0.151; [0.123] mSv. These values are higher than 3rd quartile values obtained for the right eye region. Among the simultaneously monitored regions with both dosimeters, the highest dose values were recorded in the left ankle, followed by thorax, left eye region and right eye region. Conclusions: The doses measured in chest level (without the lead apron) are about 18% higher than the measurements in the left eye region at ATC and CATE procedures, considering the 3rd quartile data. The results allow to conclude that an effective dose control in thorax region can contribute to estimate the dose on crystalline (without lead glasses). The results of our study demonstrate that in CATE and ATC procedures, without any additional eye protection, the 3rd quartile values to this region were, respectively: 0.10 e 0.15 mSv/procedures. It means that the professional can perform 200 (CATE) or 130 procedures (ATC) per year in order to avoid doses in the crystalline higher than the 20 mSv/year. For higher workload it is essential to use collective and individual protection devices.